Phenological variability and resistance to late spring frost of common beech in the international provenance test in Bosnia and Herzegovina - Memišević Hodžić, Mirzeta (Acta silvae et ligni, 2021)
The research aimed to determine the start, end and duration of leafing phases, the degree of plant damage caused by late spring frost, and the retention of leaves in autumn. The research was conducted in the international common beech provenance test in Bosnia and Herzegovina. The test contains eight provenances from Bosnia and Herzegovina, four from Germany, three from Serbia, two each from Croatia, Romania and Switzerland, and one from Hungary. Leafing phenology, canopy damage caused by late spring frost, and leaf retention were assessed in 2019. Most provenances started opening buds on 17 April 2019. Complete canopy damage affected the highest percentage of plants in provenance BW Bad Wildbad, Germany (68 %), and the lowest in provenance Konjuh Kladanj, Bosnia and Herzegovina (3.2 %). Provenance Herzogenbuchsee from Switzerland had the highest percentage of winter leaf retention (37.5 % of plants). The results can be used in choosing provenances that are resistant to low temperatures in zones of late spring and early autumn frost.
Keywords: common beech; fenofaze razvoja listov; frost damage; international provenance test; leafing phenophases; mednarodni provenienčni poskus; navadna bukev; škoda po zmrzali; winter leaf retention; zimska retencija listja